The effects of two HDR brachytherapy schedules in locally advanced cervical cancer treated with concurrent chemoradiation: A study from Chiang Mai, Thailand - Ekkasit Tharavichitkul (2018)
Efficacy of different schedules of HDR brachytherapy in concurrent chemoradiotherapy was evaluated. The study compared the effectiveness of the two HDR brachytherapy schedules which have the same Biological Effective Dose (BED) in locally advanced cervical carcinoma that was treated with concurrent chemoradiotherapy. Included in the study were 377 randomly selected patients with advanced carcinoma of the cervix uteri who were treated during the period 2004-2006. Patients were divided into Group I: 7.2 Gy × 3 fractions and Group II: 6 Gy × 4 fractions. With a median follow-up time of 35 months, local control, disease-free survival and overall survival rates were 80.8%, 63.4%, 98.8% in group I and 86.7%, 63.8%, 97.3% in group II, respectively. There was no statistical significance in terms of local control, disease- free survival, overall survival and complication rates between the two treatment schedules which could be observed. Seven patients in group I developed acute grade 2-4 GI toxicities and two patients in group II. In GU toxicities, there were three patients in group I and three patients in group II who developed grade 2-4 toxicities. In late toxicity, no patient developed grade 3-4 GU toxicities in group I while two patients developed grade 3-4 GU toxicities in group II. In GI toxicities, there were five and six patients in group I and group II, respectively, who developed grade 3-4 severity. Both HDR schedules seem to be safe and effective for the treatment of locally advanced cervical cancer.